Effect of torsional ground motion on the seismic response of multistorey buildings on different soil mediums - Bhat, Javed Ahmad; Ramana, G.V.; Nagpal, A.K.; Kamatchi, P. (Journal of Structural Engineering, 2024)
The spatial variation of ground motion due to phase lag and coherency loss effect gives rise to rotational/torsionalground motions thereby inducing additional torsional deformations. For multistorey buildings, a systematic studyis reported on the effect of torsional ground motion resulting from the propagation of motion through different soilmediums: firm soil and medium-firm soil. For these soil mediums, two cases of ground motion: (i) translation groundmotion only and (ii) combined translation and torsional ground motion are considered. For torsional ground motiontwo sets of the angle of incidence of propagating waves with vertical, 10° and 20° based on recorded values at sites, areconsidered. A set of twelve multistorey buildings comprising of frames or frames and shear walls is considered. Thesechosen buildings cover practically the entire spectrum of torsionally flexible and torsionally stiff low rise buildings.Variation of increase in storey shears along the height is studied and it is found that this variation due to torsionalground motion for some frame shear wall buildings is non-uniform along the height. Further, it is found that theincrease in the response is significant for buildings, having low fundamental translational periods of vibration and thatare torsionally flexible.